Evaluation of c-reactive protein in breast cancer by enzyme linked immunoassay technique - Ambreen Usmani; Mehreen Lateef (Journal of the Pakistan Medical Association, 2020)
Objective: To explore the serum levels of C-reactive protein in breast cancer patients, and to investigate the relationship between inflammation and progression of breast cancer. Methods: The case-control study was conducted at Bahria University Medical and Dental College, Karachi, from September 2015 to December 2018, and comprised breast cancer patients in group A and and an equal number of age-matched healthy women in control group B. C-reactive protein levels were evaluated in serum samples using enzyme-linked immunosorbent assay in both the groups and micro ribonucleic acid levels in serum were quantified using real time polymerase chain reaction. Data was analysed using SPSS 16. Results: Of the 170 subjects, 85(50%) were in each of the two groups. C-reactive protein and micro ribonucleic acid expression were significantly different in group A (p<0.001). There was no correlation (r = 0.162, p>0.01) between the tumour markers in group B (p>0.05). Conclusion: Significantly raised C-reactive protein levels showed there was a link between inflammation and breast cancer. Key Words: Breast cancer, C-reactive protein, MicroRNA 16. Continuous....